IMPLEMENTASI CORPORATE SOCIAL RESPONSIBILITY - PENINGKATAN PROFITABILITAS PT BERKAH RONA KARYA NUSANTARA CIMAHI - Rosmiati, Mia; Berliana, Citra (Indonesian Accounting Research Journal, 2024)
Corporate Social Responsibility (CSR) is a form of responsibility that must be carried out by the company to the surrounding environment. By doing social responsibility to the environment, the company will definitely get the benefits of it. This study aims to analyze the implementation of corporate social responsibility (CSR) in an effort to increase the profitability of PT Berkah Rona Karya Cimahi. The method used in this research is descriptive qualitative. Data analysis techniques taken in this study are data reduction, data presentation and conclusion. The results showed that PT BRKN has not fully implemented CSR principles based on ISO 26000. The implementation of CSR at PT BRKN also does not have an impact on the company's profits.